Zur Beschreibung der Fachsprachen für den gesteuerten Fremdsprachenunterricht - SKOWRONEK, Barbara (Wydawcnictwo Naukowe UAM, 1986)
Along with the increase in the interest of linguistic research with reference to the phenomena of linguistic performance, more attention has been paid to the specialistic languages. The present article deals with considerations concerning the description (definition) of specialist languages. On the basis of research approaches mainly of Hoffman (definition) of specialist languages. On the basis of research approaches mainly of Hoffmann and Bungarten the author draws conclusions for the teaching of special language as a foreign language.